Vitamin E in New‐Generation Lipid Emulsions Protects Against Parenteral Nutrition–Associated Liver Disease in Parenteral Nutrition–Fed Preterm Pigs. (16th January 2015) - Ng, Kenneth; Stoll, Barbara; Chacko, Shaji; Saenz de Pipaon, Miguel; Lauridsen, Charlotte; Gray, Matthew; Squires, E. James; Marini, Juan; Zamora, Irving J.; Olutoye, Oluyinka O.; Burrin, Douglas G.
Abstract : Introduction: Parenteral nutrition (PN) in preterm infants leads to PN‐associated liver disease (PNALD). PNALD has been linked to serum accumulation of phytosterols that are abundant in plant oil but absent in fish oil emulsions. Hypothesis : Whether modifying the phytosterol and vitamin E composition of soy and fish oil lipid emulsions affects development of PNALD in preterm pigs. Methods : We measured markers of PNALD in preterm pigs that received 14 days of PN that included 1 of the following: (1) Intralipid (IL, 100% soybean oil), (2) Intralipid + vitamin E (ILE, d‐α‐tocopherol), (3) Omegaven (OV, 100% fish oil), or (4) Omegaven + phytosterols (PS, β‐sitosterol, campesterol, and stigmasterol). Results : Serum levels of direct bilirubin, gamma glutamyl transferase, serum triglyceride, low‐density lipoprotein, and hepatic triglyceride content were significantly lower ( P < .05) in the ILE, OV, and PS compared to IL. Hepatic cholesterol 7‐hydroxylase and organic solute transporter–α expression was lower ( P < .05) and portal plasma FGF19 higher in the ILE, OV, and PS vs IL. Hepatic expression of mitochondrial carnitine palmitoyltransferase 1A and microsomal cytochrome P450 2E1 fatty acid oxidation genes was higher in ILE, OV, and PS vs IL. In vivo 13 C‐CDCA clearance and expression of pregnane X receptor target genes, cytochrome P450 3A29 and multidrug resistance‐associated protein 2, were higher in ILE, OV, and PS vs IL. Conclusions : α‐tocopherol in Omegaven and added to Intralipid prevented serum and liver increases in biliary and lipidemic markers of PNALD in preterm piglets. The addition of phytosterols to Omegaven did not produce evidence of PNALD.